Liver During The Coronavirus Epidemic (Eurasian Research Bulletin, 2024)
There are numerous ways in which coronavirus infection can adversely affect the liver. One notable aspect is the virus's use of the angiotensin-converting enzyme 2 (ACE-2) receptor to infiltrate cells, particularly cholangiocytes, indicating the liver as a potential target. Research from the 2002 SARS outbreak revealed liver abnormalities such as increased mitotic cells and hepatocyte damage, suggesting virus-induced apoptosis and liver injury. Early-stage SARS-CoV infections were associated with abnormal levels of cytokines and chemokines, notably elevated IL-1, IL-6, and IL-10, indicating a correlation between liver damage and inflammatory responses. Patients with chronic liver diseases exhibited higher cytokine levels, potentially exacerbating liver injury during coronavirus infection. Moreover, patients co-infected with hepatitis B or C viruses demonstrated increased hepatitis virus replication and resistance to liver injury reversal